PENGARUH KEGIATAN MELIPAT KERTAS ORIGAMI TERHADAP PERKEMBANGAN MOTORIK HALUS ANAK DI KB NURUL ISLAM SUKOKERTO JEMBER - Fitriyah, Lutfiatul; Jazuly, Ahmad; Tohedi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the effect of origami paper folding activities on the development of children's fine motor skills at KB Nurul Islam Sukokerto Jember. The problem to be studied is how origami paper folding activities can affect children's fine motor skills? The purpose of this study was to determine the effect of origami paper folding activities on the fine motor skills of children aged 4-5 years in Group A KB Nurul Islam Sukokerto. The method used is a quantitative method with a pre-experimental design and using a paired sample T-test and an N-Gain Score effectiveness test, this study analyzed data obtained from the pre-test and post-test of children's fine motor skills before and after participating in origami paper folding activities. Based on the results of research conducted at KB Nurul Islam Sukokerto Jember, origami paper folding activities have a significant effect on the development of fine motor skills in children aged 4-5 years.